Biosurfactant-assisted bio-electrokinetic enhanced remediation of heavy metal-contaminated soil - Narenkumar, Jayaraman; Das, Bhaskar; Abilaji, Subramani; Sathishkumar, Kuppusamy; AlSalhi, Mohamad S.; Devanesan, Sandhanasamy; Rajasekar, Aruliah; Malik, Tabarak (Frontiers in Microbiology, 2024)
Background Environmental soil contamination is a serious problem for humans worldwide, as it causes many diseases. Methods The present study focuses on utilizing biosurfactants produced by Pseudomonas stutzeri (P. stutzeri) NA3 and Bacillus cereus (B. cereus) EN6, as an electrolyte for removing chromium (Cr) from contaminated soil using the electrokinetic (EK) process. Results As a result, biosurfactants produced by P. stutzeri NA3 and B. cereus EN6, being lipopeptides, increase heavy metal mobility in the EK process. The Cr removal efficiency of a novel electrolyte (biosurfactants) in the EK process was compared with that of NA3 and EN6 biosurfactants. The EK results revealed a maximum Cr removal of 75 and 70% by NA3 and EN6, respectively, at the end of 7 days. Discussion The biosurfactant aids in the breaking down of the heavy metals that are present deeper into the soil matrix. From the metagenomics analysis, it was identified that biosurfactant changes the microbial community with an enhanced ability to remove heavy metals. The phytotoxicity assay confirms that NA3 biosurfactant solution showed 95% seed germination and can lower hazardous pollutants in the soil. Conclusion The application of biosurfactants as a potent electrolyte for the remediation of hazardous pollutants is an integrated process. Overall, the results of this study suggest that biosurfactants can serve as an economic and efficient electrolyte in the EK process to remove Cr from polluted soil.